2015
DOI: 10.1093/geront/gnv127
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Diversity of Successful Aging: An Operational Definition Based on 16-Year Trajectories of Functioning

Abstract: Many older adults age relatively successfully, but the character of successful functioning over time varies between indicators, and the combinations of successful indicators vary between individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 38 publications
4
60
2
4
Order By: Relevance
“…Cluster 3 'Depressed' is an intermediary group with both functional limitations and depression values between these two extremes but notable depression levels despite only physical limitations (see averages in Table 1). Clusters 1, 3, and 5 are in line with a linear and mutually reinforcing association between physical and mental health in the last years of life (Chang et al 2009;Hsu and Jones 2012;Kok et al 2015). In contrast, the 'Resilient' and 'Moderately impaired' groups both show stable low depression trajectories combined with very high and medium functional limitations, thus supporting a nonlinear interactive relationship between physical and mental health at the end of life for part of the population (RQ 1).…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…Cluster 3 'Depressed' is an intermediary group with both functional limitations and depression values between these two extremes but notable depression levels despite only physical limitations (see averages in Table 1). Clusters 1, 3, and 5 are in line with a linear and mutually reinforcing association between physical and mental health in the last years of life (Chang et al 2009;Hsu and Jones 2012;Kok et al 2015). In contrast, the 'Resilient' and 'Moderately impaired' groups both show stable low depression trajectories combined with very high and medium functional limitations, thus supporting a nonlinear interactive relationship between physical and mental health at the end of life for part of the population (RQ 1).…”
Section: Methodsmentioning
confidence: 54%
“…Findings thereby support a nonlinear interactive pattern between physical and mental health in the medium and high range of functional limitations. The 'Functional' and 'Moderately impaired' groups highlight heterogeneity within relatively high functioning aging processes and could be considered different variants of 'successful aging' (Kok et al 2015). In addition, the 'Resilient' group could be considered as successful aging in terms of psychological wellbeing despite severe functional limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies on trajectories of functional decline during various stages of the aging process have identified up to 8 different trajectories [6][7][8][9][10]. One study in 65-to 85year-olds identified 3 distinct trajectories over 10 years: one including people with substantial decline at the age of 65 years, one including people who gradually started to decline at the age of 65 years with increased progression from the age of 75 years, and one including people who did not decline until above 80 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…Most older adults value emotional functioning highly, in addition to physical functioning (Bowling & Dieppe, 2005). Following those suggestions, studies have incorporated indicators of mental health, such as depressive symptomatology, in operational definitions of successful ageing (Kok et al 2017). Even if depression is not considered to be part of successful ageing, it is strongly associated with it (Jeste et al 2013).…”
mentioning
confidence: 99%